1970
DOI: 10.1017/s1120962300025099
|View full text |Cite
|
Sign up to set email alerts
|

Twin Studies in Sport and Physical Performance

Abstract: In his recent book Dr. Roy J. Schepherd states that:“Further information of genetic effects is likely to be derived from comparisons of identical (monozygotic) and fraternal (dizygotic) twins. Gedda (1961) has already shown that identical twins are more likely to have a similar interest in sports than are fraternal twins. It would be interesting to carry out comparisons of maximum oxygen intake and other objective measurements of endurance fitness on the two classes of twins, but this crucial experiment has ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Although muscle fiber composition apparently has a major genetic component, muscle fiber area is related to training at all ages,28 and muscle strength will therefore be defined by a combination of genetic and environmental factors. Our heritability estimate for grip strength of 0.30 is consistent with results of smaller twin studies in adult men and in children 16 , 29…”
Section: Discussionsupporting
confidence: 88%
“…Although muscle fiber composition apparently has a major genetic component, muscle fiber area is related to training at all ages,28 and muscle strength will therefore be defined by a combination of genetic and environmental factors. Our heritability estimate for grip strength of 0.30 is consistent with results of smaller twin studies in adult men and in children 16 , 29…”
Section: Discussionsupporting
confidence: 88%
“…Vital capacity and total lung capacity in humans are highly related to body size. Several twin studies have suggested that there is significantly more variation between dizygotic twins (DZ) than between monozygotic twins (MZ) for vital capacity (Venerando and Milani-Comparetti, 1970;Arkinstall et al, 1974;Pirnay et al, 1975;Man and Zamel, 1976). This is generally interpreted as a significant genetic effect for the measured phenotype.…”
Section: Respiratory Functionsmentioning
confidence: 99%
“…[18][19][20][21] Heredity of muscle strength-related phenotypes was first examined in 1970. 22 In the 1970s, early twins studies calculated heritability estimates based on difference monozygotic (MZ) and dizygotic (DZ) twins for the correlation coefficient of muscle strength-related phenotypes. 14,15 This is based on the premise that MZ twins are ascribed equal genetic information; meanwhile, the genetic information between DZ twins is the same as that between siblings; that is, on average, they share about 50% of their genetic information.…”
Section: Introductionmentioning
confidence: 99%